Measurement of Carbon Stock and Soil Characteristics Reviewed from Coastline in the Mangrove Wonorejo Forest, Surabaya - Moch Arifin; Argananta Pratama Widijanto (Future Science)
This area is a mangrove forest with a natural and high plant density. The existence of mangrove forest tourism activities allows human intervention in mangrove habitat, which will have an impact on carbon storage in the soil. This research aims to determine the carbon stock in the soil in the mangrove area of Wonorejo, Surabaya. The study was conducted by surveying the land by dividing the mangrove forest land into 4 zones based on a perpendicular coastline. Environmental observations include the number of plants and the physical and chemical characteristics of the soil. The results showed that the mangroves of the Avecennia family dominated the near-shore zone and the mangroves of the Rhizophora family dominated zones 3 and 4. The growth diversity of mangroves tended to be low in each plant family, while in each zone the diversity of mangroves was at moderate levels. In soil characteristics, the texture tends to be dusty and dusty clay, with high pH, EC and Redox values. The results of the measurement of carbon stocks in the mangrove forest area ranged from 1.04 to 1.45 Mg Ha-1.